Emisi Gas Metana dan Karbon Dioksida pada Proses Pengolahan Limbah Cair Pabrik Pengolahan Kelapa Sawit PT. Bio Nusantara Teknologi Bengkulu Tengah - Linarsih Makmun; Sarto Sarto (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Emission of methane and carbon dioxide gas in the process of processing oil palm liquid waste PurposeThe purpose of this study was to know, calculate and evaluate the concentration of methane gas and carbon dioxide produced in each wastewater treatment plant (WWTP) pond.MethodThis research was a qualitative research, using case study design and explanatory approach. The object of this research was the emission of methane gas and carbon dioxide emitted from 12 WWTP ponds.ResultsThe highest COD and BOD decrement occurred in pond 4 of 39% COD and 61.2% BOD. The highest total methane gas emission was 1.49 x 109 kg hours-1 (1.49 x 106 tons hour-1) occurring in the morning, while the highest total carbon dioxide emission was 2.59 x 109 kg per hour (2.59 x 106 ton hour-1). ConclusionThe concentrations of methane and carbon dioxide gas produced by each WWTP pool varied greatly depending on temperature, residence time and the amount of mud. Methane gas emissions and carbon dioxide emissions occurred in each WWTP pool with the highest methane gas emission value occurring in pond 3 in the afternoon at 356,64 x 106 mg m-2minute-1 and the highest carbon dioxide emissions occur in pond 3 in the afternoon at 402.145 x 106 mg m-2minute-1. The decrease of COD value in whole anaerobic pool was 52,1% and the decrease of COD value in aerobic pool was 27,2%.